Android on x86: An Introduction to Optimizing for Intel® Architecture - Iggy Krajci (Apress, 2013)
Android on x86: an Introduction to Optimizing for Intel® Architecture serves two main purposes. First, it makes the case for adapting your applications onto Intel's x86 architecture, including discussions of the business potential, the changing landscape of the Android marketplace, and the unique challenges and opportunities that arise from x86 devices. The fundamental idea is that extending your applications to support x86 or creating new ones is not difficult, but it is imperative to know all of the technicalities. This book is dedicated to providing you with an awareness of these nuances and an understanding of how to tackle them. Second, and most importantly, this book provides a one-stop detailed resource for best practices and procedures associated with the installation issues, hardware optimization issues, software requirements, programming tasks, and performance optimizations that emerge when developers consider the x86 Android devices. Optimization discussions dive into native code, hardware acceleration, and advanced profiling of multimedia applications. The authors have collected this information so that you can use the book as a guide for the specific requirements of each application project. This book is not dedicated solely to code; instead it is filled with the information you need in order to take advantage of x86 architecture. It will guide you through installing the Android SDK for Intel Architecture, help you understand the differences and similarities between processor architectures available in Android devices, teach you to create and port applications, debug existing x86 applications, offer solutions for NDK and C++ optimizations, and introduce the Intel Hardware Accelerated Execution Manager. This book provides the most useful information to help you get the job done quickly while utilizing best practices.